2007
DOI: 10.1051/cocv:2007032
|View full text |Cite
|
Sign up to set email alerts
|

A relaxation result for energies defined on pairs set-function and applications

Abstract: Abstract. We consider, in an open subset Ω of R N , energies depending on the perimeter of a subset E ⊂ Ω (or some equivalent surface integral) and on a function u which is defined only on Ω \ E. We compute the lower semicontinuous envelope of such energies. This relaxation has to take into account the fact that in the limit, the "holes" E may collapse into a discontinuity of u, whose surface will be counted twice in the relaxed energy. We discuss some situations where such energies appear, and give, as an ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
42
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(43 citation statements)
references
References 17 publications
1
42
0
Order By: Relevance
“…2.38 and 2.39) to treat the presence of anisotropy in the surface term (we refer also to the recent works [3,6] for related relaxation results in higher dimension).…”
Section: − At the Points Of Its Reduced Boundary (Which Coincides Inmentioning
confidence: 99%
“…2.38 and 2.39) to treat the presence of anisotropy in the surface term (we refer also to the recent works [3,6] for related relaxation results in higher dimension).…”
Section: − At the Points Of Its Reduced Boundary (Which Coincides Inmentioning
confidence: 99%
“…Here we have chosen to present a self-contained proof based on somewhat different arguments. We should mention that the results contained in [4] have been extended and generalized in a higher dimensional setting in the two recent papers [6] and [8].…”
Section: Introductionmentioning
confidence: 99%
“…This is a formalization of an argument that is present for example in the classical approximation by elliptic functionals by Ambrosio and Tortorelli [2] or in the finite-element schemes by Chambolle and Dal Maso [14][15][16], that actually is immediately derived from [13].…”
Section: Introductionmentioning
confidence: 88%
“…An underlying feature of such approximation is that the jump set S u is 'blurred' so that it becomes a two-dimensional set, to which various approximation procedures can be applied. In a recent paper by Braides et al [13] it is shown how we can approximate E by functionals defined on pairs function-set…”
Section: Introductionmentioning
confidence: 99%